The Fair and Laissez-Faire Markets: From a Neoliberal Laissez-Faire Baseline to a Fair Market - Eric L. Dixon (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2014)
The essay begins with a brief overview of the role of the neoliberal conception of the laissez-faire market in modern political economy. The essay then goes on to defend three claims: 1) the laissez-faire version of a market should not be considered the economic ideal or baseline version of a market because often the fundamental conditions required to reach a genuine equilibrium are unfulfilled under a laissez-faire environment, 2) a distribution resultant from a laissez-faire market should not be considered the ultima facie just distributive baseline because an unregulated market may allocate commodities according to morally arbitrary factors and requires social and state support and 3) under a fair market iteration of a market government intervention and state programs may be pursued in order to fulfill the fundamental conditions of a market so as to reach a genuine equilibrium and to address other fundamental social aims and moral concerns, such as distributive justice. While these claims involve the operation of markets generally, special attention is paid to the labor market as a key example.
Keywords: free market; inequality; efficiency; social justice; distributive justice; economic justice; political economy; neoliberalism; taxes; government intervention